CLINICAL FEATURES AND OUTCOME ANALYSIS OF INTRACRANIAL HYDATID CYSTS - Khan, Muhammad Mukhtar; Shah, Mewat; Khan, Abdul Aziz; Rehman, Riaz ur; Ayub, Shahid; Ahmad, Ayaz; Aman, Atif; Shah, Muhammad Ali (Journal of Ayub Medical College Abbottabad, 2016)
Background: Hydatid cyst of the brain is a serious zoonotic parasitic infection which have profound health consequences if left untreated. The surgical excision of the cysts are rewarding for both the patient the neurosurgeon. Methods: The study was conducted prospectively at Department of Neurosurgery Hayatabad Medical Complex Peshawar from January 2013 to December 2014. Patients with a diagnosis of intracranial hydatid cysts were included, clinical and radiological features recorded, intervention and postoperative outcome were analysed. Results: Eleven patients with a male to female ratio of 1.7:1. Mean age was 12.4 (SD±6.5) years with median GCS on arrival of 10 (SD±2.5). Clinical features were headache (81.8%), vomiting (90.9%), seizures (36.4%), focal deficits (54.5%) and papilloedema (72.7%). The median GCS on discharge was 13 (SD±1.1) while GOS at 1 month follow up was 4 (SD±0.7). The bivariate analysis showed inverse correlation (R2=-0.68; p=0.02) between duration of symptoms and outcome while GCS on admission was positively correlated (rs=0.75; p=0.007) with the outcome. There was no mortality. Conclusion: Despite its rarity the clinical features are non-specific while radiological features help in establishing diagnosis. Earlier diagnosis and prompt intervention is the key to favourable outcome.